Rancangan Sistem Informasi Nilai Akademik Siswa Berbasis Web Pada Madrasah IBTIDAIYAH Darul Muttaqin Menggunakan PHP Dan MySQL - Nuzli Sakila Nurul Izni Sakila; Herlina Trisnawati; Veranita Veranita (UNIVED Press, 2025)
Academic value is a measure of student achievement at MI Darul Muttaqin in the form of a report card. The process of assessing academic values is carried out by students who come directly to MI Darul Muttaqin, based on interviews with the author and relevant parties involved in processing student academic grades. Currently, the process still uses manual methods, where homeroom teachers manage student grades from the teachers for all subjects, with the use of a considerable amount of paper. This results in errors in managing student grade data, and the process of grade management for report card filling at MI Darul Muttaqin is still hindered by the time it takes. As a solution, the design of a web-based Academic Grade Information System for students at MI Darul Muttaqin has been proposed to facilitate the homeroom teachers in managing student grades, as well as to make it easier for students to access their grades for the subjects they have taken without needing to come to the school. This system is developed using the SDLC methodology, along with a MySQL database and PHP programming language. Keywords: Software Engineering, PHP, MySQL, E-Academic Grade Information System, SDLC Methodology